Application of FAHP in gold price fluctuation factor evaluation / Norpah Mahat, Aini Mardhiah Yusuf and Siti Sarah Raseli - Mahat, Norpah; Yusuf, Aini Mardhiah; Raseli, Siti Sarah (UiTM Cawangan Perlis, 2021)
Gold has become one of the most popular and secures type of investment in our country. However, the price of gold shows a high level of volatility. This paper aims to explore the use of Fuzzy Analytic Hierarchy Process (FAHP) in evaluating and ranking the Malaysian gold price fluctuation factors. Nevertheless, there are not many researches have been done on FAHP method in gold price analysis. Hence, FAHP as tools of measurement have been applied to evaluate, compare, and rank the gold price fluctuation factors. Specifically, four factors that contribute to the volatility of gold price are determined from experts. The factors are currency exchange, demand, inflation and mining. The evaluation of FAHP shows that the highest value of normalized weight was 0.6892 for the currency factor. This study concludes that the most important factor that affects the gold price change is the currency exchange.